2015
DOI: 10.1177/1470320315584096
|View full text |Cite
|
Sign up to set email alerts
|

Association of AT1R polymorphism with hypertension risk: An update meta-analysis based on 28,952 subjects

Abstract: Background: Previous studies have shown that angiotensin II AT1 receptor gene (AT1R) polymorphisms are associated with the risk for hypertension. However, the results remain controversial. In the present study, we performed a meta-analysis to systematically summarize the association between AT1R genetic polymorphisms and the risk for hypertension. Methods: We searched the literature in PubMed, EMBASE, ISI Web of Science, Wanfang, and Chinese National Knowledge Infrastructure databases (CNKI) to find case-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
1
23
2
1
Order By: Relevance
“…We observed an association between rs5186 and hypertension, which is in contrast to findings from a meta-analysis by Liu and coworkers 46 in African Americans. Instead, Liu and associates 46 observed the rs5186-hypertension association in Asians and Caucasians in support of findings reported elsewhere.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…We observed an association between rs5186 and hypertension, which is in contrast to findings from a meta-analysis by Liu and coworkers 46 in African Americans. Instead, Liu and associates 46 observed the rs5186-hypertension association in Asians and Caucasians in support of findings reported elsewhere.…”
Section: Discussioncontrasting
confidence: 99%
“…We observed an association between rs5186 and hypertension, which is in contrast to findings from a meta-analysis by Liu and coworkers 46 in African Americans. Instead, Liu and associates 46 observed the rs5186-hypertension association in Asians and Caucasians in support of findings reported elsewhere. 45,47 Our meta-analysis also suggests an association of rs699 with hypertension, similar to studies conducted in Asians, 48,49 while no association between any of the common SNPs found in RAAS genes and hypertension has been reported by other authors.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The CC genotype is associated with an increased expression of AGTR1, with a 2.4 times higher chance of hypertension (22, 23). This polymorphism is also associated with an increased risk of renal cell carcinoma (24).…”
Section: Discussionmentioning
confidence: 99%